Distinct Business Strategy of Philceramics in Tiwi, Albay - Bile, Jamir Sebastian; Borral, Januard B.; Buela, Angel Lyka E.; Dacoco, Salve T.; Engay, Federico B.; Martirez, Katherine C. (International Journal of Research in Interdisciplinary Studies, 2025)
Pottery is one of our oldest handicrafts, but surprisingly little has changed in the past few centuries. Out of all humankind’s handicraft, pottery is the oldest. Established in 1976, PhilCeramics has been instrumental in providing training and support to potters, as well as showcasing their works through exhibitions and sales. The pottery produced by them is deeply connected to the local territory and tradition. They introduced the modern technology of pottery making in Tiwi, Albay. The researchers draw the following conclusions: Majority of the respondents are engaged in sole proprietorship form of business organization, operating 11-15 years and offering ball clay as the core of their business. Additionally, majority of them are using air dry clay as raw material in the production of ceramic products. The competitive advantage that they are practicing is sustainability. Moreover, they are focused on modern ceramic production as one of the major contributory factors in the economy. Partnership with local tourism and local government units were the predominant business strategy being practiced by the company. Market competition is the topmost challenge experienced by them in their operation. As part of the contribution of the researchers to the field of business administration a set of recommendations was crafted to address the challenges met; Improve the design and pricing; Maintaining the good quality of the product; More competitive in the marketing world; Quality of ceramics products; Innovation of facility; and Friendly tourism facility.